To the question of the self-organization of matter and the development of systems - Afandiyev, Fikrat; Islamov, Islam Ahmadaga oglu; Yusifova, Gulnare Yusif qızı (Technium Social Sciences Journal, 2022)
Each stage of the evolution of matter is associated with its self-organization. This self-organization can take forms from the simplest, elementary processes that arise in the dissipative structures of an unlimited nature, and end in its highest forms, found in the biological and social forms of movement. According to the level of such self-organization, one can judge the development of the corresponding material structures and forms of the movement of matter in general. The genetic evolution of matter and its forms is directed from the simple to the complex, from the less differentiated to the more differentiated. At the same time, old forms of symmetry are destroyed and new ones are created. This article attempts to analyze this fact and show the process of self-organization as a development. The theory of self-organization, developed within the framework of synergetic, is of great philosophical importance for understanding the specific mechanisms of development at all levels of the evolution of structures and forms of motion of matter. Self-organization is a natural-science expression of the principle of self-movement of matter, which underlies the dialectical concept of development. The dialectical concept shows and reveals the source of self-movement.